Potential of Dayak Onion (Eleutherine palmifolia (L) Merr) Extract As Antibacterial Against Pseudomonas fluorescens - Immaria Fransira; Uun Yanuhar; Maftuch Maftuch (Journal of Experimental Life Science)
Dayak onions (E. palmifolia (L) Merr) is a herb used as medicine and known to have antibacterial activity. This research aimed to evaluate antibacterial activity of Dayak onion (Eleutherine palmifolia (L) Merr) extract against fish pathogen Pseudomonas fluorescens. The method used in this study was extraction by maceration, UV-Vis spectrophotometry analysis on the extract and antibacterial activity test with Minimum Inhibitory Concentration (MIC) as well as disc diffusion test. The results of this study showed that the yield value was 8.87%. Based on UV-Vis analysis, it confirmed that extract of Dayak onion (Eleutherine palmifolia (L) Merr) contains predominantly flavonoids and phenols with its derivatives, that have antibacterial activity. The results of MIC and disc diffusion test showed potential antibacterial activity against P. fluorescens, as observed from the value of absorbance and inhibition zones that formed.